EFFICIENT FARMING AND TECHNOLOGICAL SOLUTIONS IN THE AGRICULTURAL SECTOR IN BULGARIA - E. Delcheva (Trakia Journal of Sciences)
Nowadays, the development of technology in agriculture, as in all other spheres, is extremely dynamic, innovative and progressive, but also incredibly necessary. Modern technologies and technical solutions occupy an increasingly important place and role in agriculture in Bulgaria, which is part of the world economy, which in turn is developing in a continuous process. The PURPOSE of the research is to analyze these technological solutions and innovations in the agrarian economy and bring them to lower costs, which in turn will increase profit and efficiency. A research METHOD is an analysis of the introduction of technologies through various innovative solutions such as digitization, automation, robotization, software solutions and others to help farmers renew and modernize their farms. This modernization is necessary to achieve an efficient farm and make the right technological decisions as a RESULT of the study of agro-businesses. This is necessary, as well as to deal with various problems in the agricultural sector in Bulgaria. A CONCLUSION from the implementation of innovations in the economy is that it is a good strategy for survival in the national and especially in the international market, as well as for dealing with costs and the possibility of profit. Innovation is needed to adapt to the ever-changing external environment and reduce uncertainty at all levels: international, national and regional.